VISUAL ATTENTION AND EMOTION RESPONSE IN DETECTING MOTORCYCLISTS AND CYCLISTS ELICITED VIA ANIMATION CLIPS - Dian Kemala Putri; Kemal Ade Sekarwati; Indah Mulyani (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2022)
The behavior of road users, especially motorcyclists and cyclists play an important role in the occurrence of accidents. Environmental factors on road, such as numbers of vehicles that share the same space which in turn will cause congestion to occur and other driver's behavior will affect the driver's emotional condition. The purpose of this study is to investigate car drivers’ visual attention and emotional state when detecting motorcyclists and cyclists whose presence on the streets are related to safe driving behavior. This study uses five animation clips that describe phenomenon of traffic and driving in Jakarta as the case studies. Emotional wheel (EW) is used to analyze the emotional state of the driver. Result suggests that animation clips can be a helpful tool to predict drivers’ visual attention in real life traffic scenarios. This study also indicated that unpleasant emotion can affect a driver’s attention management while driving.